The outbreak of new diseases in an era of religious and spiritual crisis: : medical humanism and the control of the body and soul as a method of medical treatment - Kavvadia, Maria (Mos Historicus: A Critical Review of European History, 2023)
The paper examines how the humanist physician and later professor of medicine at the great Universities of Italy, Girolamo Mercuriale of Forlì (1530-1606), addressed the issue of new diseases in medical as well as religious-social terms in his medical book De arte gymnastica (Venice, 1569), while he served as the personal physician of Cardinal Alessandro Farnese (1520-1589). Mercuriale’s medical gymnastics, as a medical method for the treatment of new diseases, stands out as paradigmatic, on the one hand, of the scientific-medical culture of mid-sixteenth century Rome and, on the other hand, the political-religious strategies of the Catholic Church regarding the control of body culture in the context of the Counter-Reformation.